Familial Lecithin:Cholesterol Acyltransferase Deficiency: First-in-Human Treatment with Enzyme Replacement - Shamburek, Robert D. (J Clin Lipidol, 2015)
BACKGROUND: Humans with familial lecithin:cholesterol acyltransferase (LCAT) deficiency (FLD) have extremely low or undetectable HDL-C levels and by early adulthood develop many manifestations of the disorder, including corneal opacities, anemia, and renal disease. OBJECTIVE: To determine if infusions of recombinant human LCAT (rhLCAT) could reverse the anemia, halt progression of renal disease and normalize HDL in FLD. METHODS: rhLCAT (ACP-501) was infused i.v. over 1 hour on 3 occasions in a dose optimization phase (0.3, 3.0, and 9.0 mg/kg), then 3.0 or 9.0 mg/kg every 1–2 weeks for 7 months in a maintenance phase. Plasma lipoproteins, lipids, LCAT levels, and several measures of renal function and other clinical labs were monitored. RESULTS: LCAT concentration peaked at the end of each infusion and decreased to near baseline over 7 days. Renal function generally stabilized or improved and the anemia improved. After infusion, HDL-C rapidly increased, peaking near normal in 8–12 hours; analysis of HDL particles by various methods all revealed rapid sequential disappearance of preβ-HDL and small α-4 HDL and appearance of normal α-HDL. LDL-C increased more slowly than HDL-C. Of note, triglyceride routinely decreased after meals following infusion, in contrast to the usual post-prandial increase in the absence of rhLCAT infusion. CONCLUSIONS: rhLCAT infusions were well tolerated in this first-in-human study in FLD; the anemia improved, as did most parameters related to renal function in spite of advanced disease. Plasma lipids transiently normalized, and there was rapid sequential conversion of small preβ-HDL particles to mature spherical α-HDL particles.